Maẓālim between Politics and Justice under the Mamluks - Rashad, Menna (AUC Knowledge Fountain, 2021)
This thesis aims to explore the place of the maẓālim institution in the Mamluk state and to study maẓālim as a product of its period rather than following the strict provisions of al-Māwardī’s theory. This thesis’s primary objective is to explore the place of maẓālim in the Mamluk state by identifying the extent to which this institution was politically utilized and used by rulers to assert their power in different ways. The second objective of this thesis is to study maẓālim in relation to other forms of justice: sharīʿah, siyāsah, and Yāsā. On the basis of this objective, this study adopts a periodization that focuses on moments of change. Although there was a degree of continuity, as each chapter will try to show, significant transformations marked each phase. This thesis investigates the extent to which these key developments were informed by particular political, economic, and social conditions that impacted the institution’s functioning and had broader implications for the Mamluk legal system.